Back to Tityus serrulatus Lutz & Mello, 1922 (Scorpiones: Buthidae): new comments about an old species - Wilson R. Lourenço (Journal of Venomous Animals and Toxins including Tropical Diseases, 2022)
Abstract A synopsis on the historical, geographical and ecological aspects related to the most conspicuous scorpion species of the genus Tityus known from Brazil is proposed. Tityus serrulatus Lutz & Mello, 1922 was described precisely one century ago, nevertheless many questions related to its ecological adaptations and geographical expansion remain without a precise response. This species, well known for its infamous reputation of noxious species, is also known for its capacity to reproduce asexually, by parthenogenesis. Although the individuals of a given population are considered clones, a new hypothesis could suggest the occurrence of mutations within isolated individuals, leading to distinct subpopulations that could present better phenotypic performances in ecological habitats distinct from those of the original area of distribution of the species.